2014
DOI: 10.4103/0972-3919.130299
|View full text |Cite
|
Sign up to set email alerts
|

Malaria masquerading as relapse of Hodgkin′s lymphoma on contrast enhanced 18 F-fluorodeoxyglucose positron emission tomography/computed tomography: A diagnostic dilemma

Abstract: 18Flurodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) is nowadays routinely used in management of lymphoma patients. We here present a case of Hodgkin's lymphoma which showed 18F-FDG avid splenomegaly on PET/CT done for clinically suspected relapse. Further evaluation by peripheral smear examination revealed malaria. The patient was then started on anti-malarial medications and follow-up PET/CT revealed resolution of hypermetabolic splenomegaly. This report highlights that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…As access to clinical imaging infrastructure in malaria endemic areas continues to improve, an increasing number of studies have demonstrated the utility of MRI to evaluate the brain in cerebral [ 12 ] and uncomplicated falciparum malaria [ 13 , 14 ]. In contrast, PET imaging in malaria is limited to a small number of nonhuman primate studies [ 15 , 16 ] and a single case report of serendipitous imaging in suspected lymphoma [ 17 ]. In the nonhuman primate studies, uptake of the glucose biomimetic 18-F fluorodeoxyglucose (FDG) was colocated with sequestered infected red blood cells (iRBCs) as ascertained on subsequent autopsy [ 16 ], suggesting that PET imaging using this widely available radiotracer that targets glucose utilization may be a useful modality to localize organ-specific parasite accumulation and host response in life.…”
Section: Introductionmentioning
confidence: 99%
“…As access to clinical imaging infrastructure in malaria endemic areas continues to improve, an increasing number of studies have demonstrated the utility of MRI to evaluate the brain in cerebral [ 12 ] and uncomplicated falciparum malaria [ 13 , 14 ]. In contrast, PET imaging in malaria is limited to a small number of nonhuman primate studies [ 15 , 16 ] and a single case report of serendipitous imaging in suspected lymphoma [ 17 ]. In the nonhuman primate studies, uptake of the glucose biomimetic 18-F fluorodeoxyglucose (FDG) was colocated with sequestered infected red blood cells (iRBCs) as ascertained on subsequent autopsy [ 16 ], suggesting that PET imaging using this widely available radiotracer that targets glucose utilization may be a useful modality to localize organ-specific parasite accumulation and host response in life.…”
Section: Introductionmentioning
confidence: 99%
“…As access to clinical imaging infrastructure in malaria endemic areas continues to improve, an increasing number of studies have demonstrated the utility of MRI to evaluate the brain in cerebral [12] and uncomplicated falciparum malaria [13,14]. In contrast, PET imaging in malaria is limited to a small number of nonhuman primate studies [15,16] and a single case report of serendipitous imaging in suspected lymphoma [17]. In the nonhuman primate studies, uptake of the glucose biomimetic 18-F fluorodeoxyglucose (FDG) was colocated with sequestered infected red blood cells (iRBCs) as ascertained on subsequent autopsy [16], suggesting that PET imaging using this widely available radiotracer that targets glucose utilization PLOS MEDICINE may be a useful modality to localize organ-specific parasite accumulation and host response in life.…”
Section: Introductionmentioning
confidence: 99%